Cellular senescence in acute human infectious disease: a systematic review - Miller, William C.; Wallace, Stephanie; Kamm, William; Reardon, Erin; Theis-Mahon, Nicole; Yousefzadeh, Matthew J.; Schmidt, Elizabeth L.; Niedernhofer, Laura J.; Puskarich, Michael A. (Frontiers in Aging, 2024)
IntroductionAcute infectious disease represents a significant cause of mortality and morbidity in elderly individuals admitted to the hospital. In its extreme, it presents as sepsis, a systematic inflammatory and immunologic response responsible for self-injurious organ injury. As individuals age, a unique set of factors including immunosenescence predispose them to acquiring an infection and a worse clinical prognosis. This systematic review explores the relationship between cellular senescence, an age-related inflammatory phenomenon, with acute human infectious disease.MethodsEmbase via OVID, Scopus, Web of Science, Global Index Medicus, Cochrane Library via Wiley, and ClinicalTrials.gov were queried. Included studies must have compared at least one of the following measures of cellular senescence between patients with an infection and without an infection: cell cycle inhibition measured via levels of p16INK4a and/or p21CIP1, short telomere length, DNA damage via ɣH2AX, high senescence-associated β galactosidase activity, and inflammation via the detection of senescence associated secretory phenotype (SASP). Manuscripts were screened and data collected via two independent reviewers.ResultsA total of 15,828 studies were screened after duplicates were removed. One hundred and fifty-three full-text articles were assessed for eligibility and a total of 16 original articles were included in analysis. Of the 16 original articles included, 12 (75%) articles were centered on SARS-CoV-2, 2 (12.5%) articles utilized patients infected with Leishmania braziliensis, 1 (6.25%) with Plasmodium falciparum, and 1 (6.25%) with Hepatitis C.ConclusionCurrent literature demonstrates robust upregulation of markers of cellular senescence in the setting of acute SARS-CoV-2, P. falciparum, L. braziliensis, and hepatitis C virus, and that markers of senescence correlate with disease severity and persist for months after resolution. Limitations in the number and types of infectious organisms studied, low sample sizes, modest longitudinal sampling, and a lack of consistency in markers measured, the method of measurement, and the definition of normal values represent ongoing gaps in the literature.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=421473, Identifier CRD42023421473.